Settlement of Industrial Relations Disputes and Termination of Work Relations according to the Applicable Legislation - Pramono, Agus (Universitas Islam Negeri Walisongo Semarang, 2020)
This article discusses the settlement of industrial relations disputes and termination of employment according to the applicable laws. Industrial relations disputes can be divided into two types: disputes over rights and disputes over interests. The relationship between workers and employers is a relationship that needs each other; workers need wages, employers benefit. However, in practice there are problems, so employers give Warning Letters I and II which are followed by Termination of Employment (PHK). The process of resolving this problem can be carried out through Bipartite, Mediation, or to the Industrial Relations Court. This paper is written with a normative juridical approach. The results show that the labor-employer problem is getting more complicated since the existence of the Omnibus Law on Job Creation, one of which contains the elimination of the city / district minimum wage (UMK) and replaced with the provincial minimum wage (UMP). The elimination of MSEs results in lower wages for workers. In fact, in the Manpower Act Number 13 of 2003, no worker may receive a wage below the minimum wage, because the determination of wages is based on the calculation of Living Needs.[]Artikel ini membahas mengenai penyelesaian perselisihan hubungan industrial dan pemutusan hubungan kerja menurut perundang-undangan yang berlaku. Perselisihan hubungan industrial menurut jenisnya dapat dibagi menjadi dua: perselisihan hak dan perselisihan kepentingan. Hubungan pekerja dan pengusaha merupakan hubungan yang saling membutuhkan; buruh memerlukan upah, pengusaha mendapatkan keuntungan. Namun, dalam prakteknya terjadi permasalahan, sehingga pengusaha memberikan Surat Peringatan I dan II yang diikuti dengan Pemutusan Hubugan Kerja (PHK). Proses penyelesaian persoalan ini dapat dilakukan melalui Bipartit, Mediasi, atau ke Pengadilan Hubungan Industrial. Tulisan ini ditulis dengan pendekatan yuridis normatif. Hasil penelitian menunjukkan bahwa permasalahan buruh-pengusaha semakin pelik seja hadirnya Undang-Undang Omnibus Law Cipta Lapangan Kerja yang salah satu isinya penghapusan upah minimum kota/kabupaten (UMK) dan diganti dengan upah minimum provinsi (UMP). Penghapusan UMK membuat upah pekerja lebih rendah. Padahal, dalam Undang-Undang Ketenagakerjaan Nomor 13 Tahun 2003 tak boleh ada pekerja yang mendapat upah di bawah upah minimum, karena penetapan upah didasarkan atas perhitungan Kebutuhan Layak Hidup.